Gestão da tecnologia da informação nas Instituições de Ensino Superior - Alves, Claudia Fontes Magalhães (2006)
The use of information technology (IT) in modern times shows the human being s effort to try to overcome the geographical separation that still exists between people and the institutions. This has been happening through the new ways of communication. As a result of social interactions, the higher education institutions are being stimulated more and more by the technological development, in order to assimilate the changes in this field. This study brings an approach about the management of IT in a private higher education institution from Salvador. Its ultimate purpose is to identify the aspects related to the use of this technology in the chosen institution, emphasizing the use of Internet with a view to research and training, the technological infrastructure provided by the institution, the availability of investment, the degree of satisfaction of the information systems users, the benefits and the alignment of IT with the strategic planning of the institution. The importance of this study is due to the fact that Brazilian society is living a period of changes, in which the IT has been seen as one of the boosters of these changes. According to this conception, it is easy to see the importance of the higher education institutions working as producers and disseminators of knowledge. And this was a determining fact to choose the object of this study. As a methodological procedure, a qualitative approach was adopted through the study of a single case in a private higher education institution from Salvador, the Faculdade Baiana de Ciências (Fabac). The data were collected by means of interviews and questions, while the population and the deliberate sample were composed of corporative managers, teachers, students and professionals involved with administrative work. In general, the study enabled to come to a deeper knowledge of the computerization process of the Fabac, and also it was possible to verify, through the seven categories of analysis adopted, the interest of the institution in investing in IT, the availability of investment and the relation cost-benefit that determines the implementation of new solutions. Besides, the study points the urgent need of a review in the technological infrastructure of the higher education institutions, including computer labs, the investment in training and the need of having the IT working aligned with the strategic planning of the organization.